Mode I delamination simulation using LS-DYNA - Ibrahim, Mohamed S.; Hussain Shah, Qasim (IIUM Press, 2011)
There are several failure models that can be used to predict delamination and these include stress based failure models, fracture mechanics and damage mechanics. The damage mechanics combines the advantages of stress based and fracture mechanics into a single failure model. In LS-DYNA the damage mechanics based failure models are available through material models MAT_138 investigate mode I delamination. Results are presented on the accuracy of both failure models.